ChemInform Abstract: Orchestrated Triple C—H Activation Reactions Using Two Directing Groups: Rapid Assembly of Complex Pyrazoles. Issue 26 (June 2015) - Yang, Weibo; Ye, Shengqing; Fanning, Dewey; Coon, Timothy; Schmidt, Yvonne; Krenitsky, Paul; Stamos, Dean; Yu, Jin‐Quan
Abstract A sequential triple C—H activation reaction directed by a pyrazole and an amide group leads to the well‐controlled construction of sterically congested dihydrobenzo[e]indazole derivatives.